Hubungan Depresi dengan Kemampuan Dalam Aktivitas Dasar Sehari-Hari Pada Lanjut Usia di Panti Sosial Tresna Werdha Minaula Kendari - Dimas Aji Pamungkas; Tomy Nurtamin; Junuda Junuda (Halu Oleo University, 2016)
According to PPDGJ-III depression is a mental disorder that has three major symptoms of depressive affect, loss of interest and easily tired state, and has seven other symptoms such as reduced concentration, reduced confidence, feelng of guilty, pessimistic, suicidal ideas, sleep disturbance and loss of appetite. These problem could be acute or chronic and lead impaired ability of individuals in everyday activities. Activity Daily Living is work activities of daily routine. Activity Daily Living is a staple for self-care activities. These study aims to determine the relationship between depression and activity daily living the elderly in Panti Sosial Tresna Werdha “Minaula” Kendari. These study was an observational analytic study with cross sectional design. The population from elderly in Panti Sosial Tresna Werdha